2007
DOI: 10.17796/jcpd.31.4.v762053488031141
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Molar Fissures by Cone-Beam Tomography

Abstract: This study aimed to validate clinical analysis of 20 pediatric dentists on occlusal groove-fossa-system of molar depth comparing to Cone-beam tomography. The 48 sound third molars were visually classified from the shallowest to the deepest. Images were taken from the Accuitomo 3DX. There was a fair correlation between clinical analysis and the tomographic scorings (rs= 0.238; P=0.103). It was concluded that pediatric dentists were not able to classify the fissures depth by visual analysis correctly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Another factor that affects caries progression in deep and narrow fissures is the closeness of these fissures to the dentinoenamel junction (DEJ). The distance between the deepest part of the fissure and the DEJ affects the progression of caries (23). Consequently, fissure caries can easily initiate and involve dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that affects caries progression in deep and narrow fissures is the closeness of these fissures to the dentinoenamel junction (DEJ). The distance between the deepest part of the fissure and the DEJ affects the progression of caries (23). Consequently, fissure caries can easily initiate and involve dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Je obtížné stanovit, zda laryngoskopie jsou významným etiologickým faktorem vzniku VVS, protože se obvykle provádí u dětí předčasně narozených s VNPH a ENPH, u nichž jsou v postnatálním období diagnostikována závažná onemocnění. Pravděpodobně lokální i systémové faktory působí společně, a proto je velmi problematické, či dokonce nemožné určit etiologický faktor, který by byl nejsilněji spojen s VVS [25].…”
Section: Závěrunclassified
“…There are many investigations reporting different protocols for cleaning P&F 2 and for sealant application [3][4][5] . In a study published in 2007, Cruvivnel et al 6 suggested that the depth of P&F is the most critical factor in terms of possible pulpal involvement. They showed that the permanent dentition, the deepest part of the P&F is frequently located near or in direct contact with the enamel-dentine junction.…”
Section: Introductionmentioning
confidence: 99%